Genosida Terhadap Warga Sipil: Evaluasi Terhadap Mekanisme Akuntabilitas Hukum Secara Internasional - Pesona Bias Pelangi Karina Putri; Adelia Adelia; Ganis Vitayanty Noor; Loso Loso (Lembaga Pengembangan Kinerja Dosen, 2025)
Genocide against civilians constitutes a severe infringement upon fundamental human rights, demanding a firm response from the international community. This crime not only causes immense suffering for its victims but also poses a serious threat to global stability. Legal accountabillity for perpetrators of genocide is a crucial aspect pertaining to the global framework of international law. In this articles evaluates the mechanisms of legal accountability, highlighting the effectiveness, challenges, and opportunities faced by Judicial bodies like the International Criminal Court (ICC) and temporary tribunals such as the ICTR and ICTY. By examining genocide incidents from the 20th and 21st centuries, the research highlights various shortcomings in the accountability framework, such as political interference, inconsistent legal enforcement, and insufficient international collaboration from member states in extraditing suspects. Legal and administrative obstacles, such as evidence collection and witness protection, also hinder judicial processes. Nevertheless, there are opportunities to enhance the system’s effectiveness, including strengthening the authority of international judicial bodies, improving inter-state coordination, and utilizing technology in genocide investigations. By addressing these shortcomings, the international legal system is expected to become more effective in upholding justice and preventing future acts of genocide.